Improvement of storage stability of barley, buckwheat and lupin composite flour by microwave treatment and its influence on functional properties of bread - Olcay, Hatice Sena; Ozulku, Gorkem (ELSEVIER, 2025)
The aim of this study was to substitute wheat flour with barley, buckwheat and lupin flour mixture to design nutritional bread formulation that meets expectations of today's consumer. However, storage stability of such flour mixtures is problem for manufacturers. The effect of microwave (MW) treatment (350 W-700 W power levels and 30 s-90 s-150 s exposure times) on flour and bread properties was investigated to overcome this problem. Bread with maximum specific volume and minimum hardness was obtained from formulation of 10 % barley flour, 37.5 % buckwheat flour and 2.5 % lupin flour by using D-optimal mixture design. The lowest free fatty acid and total yeast-mold were obtained from 700 W-150 s treatment. MW treatment increased total phenolic content and antioxidant activity while decreased total yeast-mold of flours and breads. Although MW treatment increased hardness of breads, no statistically significant difference was found between specific volume, springiness, cohesiveness, chewiness, water evaporation enthalpy.
Keywords: Flour blend; Microwave; Optimization; Storage study; WHOLE-WHEAT-FLOUR; ANTIOXIDANT ACTIVITY; ASSAYS; Chemistry; Food Science & Technology